Proteomic analysis of liver from finishing beef cattle supplemented with a rumen-protected b-vitamin blend and hydroxy trace minerals - Lopes, Mariana Mescouto; Brito, Thaís Ribeiro [UNESP]; Lage, Josiane Fonseca; Costa, Thaís Correia; Fontes, Marta Maria Dos Santos; Serão, Nick Vergara Lopes; Mendes, Tiago Antônio de Oliveira; Reis, Ricardo Andrade [UNESP]; Veroneze, Renata; E Silva, Fabyano Fonseca; Duarte, Marcio de Souza (MDPI, 2021)
Vitamin B and trace minerals are crucial molecular signals involved in many biological pathways; however, their bioavailability is compromised in high-producing ruminant animals. So far, studies have mainly focused on the effects of these micronutrients on animal performance, but their use in a rumen-protected form and their impact on liver metabolism in finishing beef cattle is poorly known. We used a shotgun proteomic approach combined with biological network analyses to assess the effects of a rumen-protected B-vitamin blend, as well as those of hydroxy trace minerals, on the hepatic proteome. A total of 20 non-castrated Nellore males with 353 ± 43 kg of initial body weight were randomly assigned to one of the following treatments: CTRL—inorganic trace minerals without supplementation of a protected vitamin B blend, or SUP—supplementation of hydroxy trace minerals and a protected vitamin B blend. All animals were fed the same amount of the experimental diet for 106 days, and liver biopsies were performed at the end of the experimental period. Supplemented animals showed 37 up-regulated proteins (p < 0.10), and the enrichment analysis revealed that these proteins were involved in protein folding (p = 0.04), mitochondrial respiratory chain complex I (p = 0.01) and IV (p = 0.01), chaperonin-containing T-complex 2 (p = 0.01), glutathione metabolism (p < 0.01), and other aspects linked to oxidative-stress responses. These results indicate that rumen-protected vitamin B and hydroxy trace mineral supplementation during the finishing phase alters the abundance of proteins associated with the electron transport chain and other oxidation–reduction pathways, boosting the production of reactive oxygen species, which appear to modulate proteins linked to oxidative-damage responses to maintain cellular homeostasis.
Keywords: Beef cattle; Hydroxyl trace minerals; Liver metabolism; Proteomics; Vitamin B